slope = rise/run = -2/1 = -2.
The slope of f(x) is -2, while the slope of g(x) is -6.
Since -2 is a greater number than -6, the answer is:
C) The slope of f(x) is greater than the slope of g(x).
rise = change in y-direction = Δy
run = change in x - direction = Δx
Δy y2 - y1 [1 - 3] - 2
slope = = = = - 2
Δx x2 - x1 [1 - 0] 1
2) The slope of the funtion g(x) defined as - 6x - 5 is the coefficient of x, which is - 6.
So, compare: - 2 > - 6, i.e. the slope of f(x) is greater than the slope of g(x).
Anxwer: the slope of f(x) is greater than the slope of g(x)
( ͡° ͜ʖ ͡° ) copy and paste it
lets say, first number = x
second number = 3x+7
total = 49
4x+7 = 49
4x = 42
x = 42/4
3x+7 = 3(10.5)+7 = 93.8